Sustainability Balanced Scorecard (SBSC) as a Performance Measurement of Corporate Sustainability - Novitasari, Eni; Syahrir, Nurwahyuni; Ichsan, Hisyam (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The purpose of this research is to examine the performance assessment technique of corporate sustainability, which is based on measurement using the Sustainability Balanced Scorecard (SBSC) perspective. The SBSC is an evolved performance measurement framework of the Balanced Scorecard (BSC), originally developed by Kaplan and Norton in 1996. This SBSC measurement incorporates four perspectives adopted from the BSC, but further enhanced with environmental performance indicators. The four aspects of the SBSC include the financial perspective, stakeholder perspective, internal process perspective, and learning and growth perspective. For this study, the researchers employed a qualitative descriptive research approach, analyzing the conceptual framework of SBSC developed by Nikolaou in 2013. The research focused on pharmaceutical companies listed on the Indonesian Stock Exchange (IDX) as the subject of investigation. The research findings revealed that the conceptual framework for sustainability performance assessment developed by Nikolaou can be effectively employed as a reliable and transparent means of evaluating sustainability performance